2013
DOI: 10.1175/jpo-d-12-0197.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface Wave Effects on High-Frequency Currents over a Shelf Edge Bank

Abstract: Several acoustic Doppler current profilers and vertical strings of temperature, conductivity, and pressure sensors, deployed on and around the East Flower Garden Bank (EFGB), were used to examine surface wave effects on high-frequency flows over the bank and to quantify spatial and temporal characteristic of these high-frequency flows. The EFGB, about 5-km wide and 10-km long, is located about 180-km southeast of Galveston, Texas, and consists of steep slopes on southern and eastern sides that rise from water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Here, the drawdown of the pycnocline and subsequent generation of upslope-propagating boluses have the potential to induce BBL turbulence and resuspension (Figure 7c). The effect of surface wave-induced currents is nonnegligible in this region (e.g., Wijesekera et al 2013), but this effect remains unexplored in simulations. Boluses have been modeled by several authors, with 3D simulations by Arthur & Fringer (2014) providing…”
Section: Direct Numerical Simulation (Dns)mentioning
confidence: 99%
“…Here, the drawdown of the pycnocline and subsequent generation of upslope-propagating boluses have the potential to induce BBL turbulence and resuspension (Figure 7c). The effect of surface wave-induced currents is nonnegligible in this region (e.g., Wijesekera et al 2013), but this effect remains unexplored in simulations. Boluses have been modeled by several authors, with 3D simulations by Arthur & Fringer (2014) providing…”
Section: Direct Numerical Simulation (Dns)mentioning
confidence: 99%
“…High values of ε , which easily reached 10 −6 W kg −1 , were also found near the bottom of the EFGB as well as near the sea surface (above 10 m; Figures and ). Near‐surface turbulence seemed to be partially related to the daily temperature cycle since winds were rather weak and surface waves were small and not breaking (surface wave significant heights were less than 0.5 m [ Wijesekera et al ., ]). Additionally, estimates of the Kolmogorov scale ( L O = ε 1/2 N − 3/2 ) indicated that length scales of turbulent overturns in the EFGB region were less than 1 m (99% of L O estimates ≤ 1).…”
Section: Turbulence and Mixingmentioning
confidence: 99%
“…This experiment builds on technicalscientific relationships established with NRL for the Mixing Over Rough Topography experiment in the Gulf of Mexico (MORT; Wijesekera et al, 2013).…”
Section: Related Projectsmentioning
confidence: 99%